Neuropathy in paediatric type 1 diabetes mellitus: clinical characterization and analysis of risk factors in the diabetes prospective follow-up registry DPV (Diabetes-Patienten-Verlaufsdokumentation)-registry - Pappa, Angeliki; Haeusler, Martin G.; Tittel, Sascha R.; Boettcher, Claudia; Hilgard, Doerte; Knauer-Fischer, Sabine; Pavel, Marianne; Woelfle, Joachim; Holl, Reinhard W. (The journal of pediatric endocrinology and metabolism, 2023)
Objectives Data on the prevalence, clinical features and risk factors associated with paediatric diabetic neuropathy (DN) are scarce. Methods We retrospectively analysed data from the DPV registry, including patients under 20years of age, treated for type 1 diabetes mellitus (T1D) between 2005 and 2021. Patients with non-diabetic neuropathy were excluded. Data came from centres in Austria, Germany, Luxembourg and Switzerland. Results 1,121 of the 84,390 patients included had been diagnosed with DN. Univariate analysis showed patients with DN to be older and predominantly female, with a longer duration of T1D, higher insulin dosages per kg and day, lower rates of insulin pump therapy, higher postprandial glucose-, higher HbA 1c -and higher cholesterol levels, and higher diastolic and systolic blood pressure values. There was also a larger proportion of smokers and higher prevalence of diabetic retinopathy. Median duration of diabetes at diagnosis of DN was 8.3years. Multivariable analysis, adjusted for demographics revealed an increased risk for DN among female patients and those who were older, underweight (BMI-SDS), smoked cigarettes or had a longer duration of T1D or higher levels of HbA 1c and postprandial blood glucose. The presence of retinopathy and higher cholesterol levels were also linked to increased risk while not-using insulin pump therapy was not. Conclusions DN can develop after just a short duration of T1D. Prevention may be achieved by a lowering of HbA 1c -and postprandial glucose levels through improved glycaemic control. This warrants further investigation. The slight female predominance suggests further hormonal and genetic etiological factors.